Sarcoptic Scabies Disease and Treatment Methods (Texas Journal of Medical Science, 2023)
Scabies, caused by the Sarcoptes scabiei mite, is a highly contagious skin infestation that affects millions of people worldwide. It is characterized by intense itching, redness, and the presence of burrow tracks on the skin. Effective treatment methods are essential to alleviate symptoms and eradicate the mite infestation. This article discusses the disease and various treatment options available